Case reports of a typical extrafollicular adenomatoid odontogenic tumor of maxilla - Kumar, Annem Sudarshan; Sameera, Ayesha; Reddy, Sridhar Erugula; Roja, Karri Lakshmi; Nelakurthi, Hasini; Haritha, Pothuraju (International Journal of Contemporary Pediatrics, 2018)
Adenomatoid odontogenic tumor is a rare benign odontogenic tumor comprising of 3% to 7% of all Odontogenic tumors. It is usually asymptomatic, well circumscribed, slow growing tumor associated often with impacted canine and discovered on routine radiographs. Microscopically this lesion shows a variety of patterns forming sheets, strands, nest or rosette-like structures with ductal pattern with central space surrounded by single layer of cuboidal to columnar epithelial cells with a rim of eosinophilic coagulum which is the characteristic feature of these tumors. In this article we present two extrafollicular cases of this rare tumor occurring in a male and a female patient in the maxillary anterior region with both symptomatic and asymptomatic presentation. Both the tumors were not associated with any impacted tooth. Adenomatiod Odontogenic tumor was confirmed based on histopathology.